(untitled) (Research, Society and Development, 2022)
Periodontal plastic surgery has been recommended for patients who are dissatisfied with their smile or disproportionate to their gingival anatomy, so its correct identification is crucial to plan the most appropriate treatment procedure and provide greater predictability of success. Therefore, the present work aims to demonstrate, through a clinical case report, the correction of the gummy smile through a minimally invasive technique called flapless. Patient, caucasian, female, 31 years old, has as main complaint dissatisfaction with the size and appearance of her teeth when smiling. After clinical evaluation, it was decided to perform the surgery to increase the clinical crown using the flapless technique. After 45 days of the procedure, complete healing of the tissues was observed, and from the probing depth examination, the effectiveness of the conquest of the biological space could be confirmed. In view of the aforementioned case, it was observed that the correction of dentogingival asymmetry by the flapless technique (flapless) is a safe, easy and predictable procedure, which has several positive points, among them: less bleeding and surgical time, decrease in inflammation in the postoperative period. surgery, no need for suturing and minimal discomfort during recovery. Its feasibility and clinical applicability is notorious, with reduced chances of recurrence and a high rate of final success.